Looking at the big picture: using systems theory to understand the impact of body-worn cameras on police accountability - Petersen, Kevin (Critical criminology, 2022)
The widespread adoption of body-worn cameras (BWC) began amid public pressure for police accountability following a series of highly publicized use-of-force incidents. Extant BWC research primarily associates the concept of police accountability with the prevalence of police misconduct alone, often focusing on quantitative changes in citizen complaints and use-of-force reports. However, perceptions of accountability following unjustified use-of-force incidents are shaped not only by the prevalence of police misconduct, but also by the broader systemic response, including the way in which the mechanisms of arrest, prosecution, and sentencing are applied to unjust police behavior. This article proposes a systems approach to police accountability in the context of BWCs. Such an approach considers the outcomes of police, prosecution, court, and corrections agencies as equally important to the achievement of accountability. To understand the impact of BWCs on police accountability, their effect on the entire criminal justice system should be considered.